Operations and Supply Chain Management - Collier, David A.; Evans, James R. (Cengage, 2024)
This edition balances coverage of both manufacturing and service businesses with the latest updates, an additional new SCM chapter and new discussions that highlight the latest changes in OM and SCM. Clear explanations are supported with contemporary examples and new and updated case studies that demonstrate how concepts apply. Discussions highlight new techniques and principles as well as the most recent Excel techniques and digital tools. Solved problems further guide you through key formulas and computations. MindTap online learning platform is available for both manual calculations and the use of Excel spreadsheet templates and models. MindTap's algorithmic homework and interactive learning tools also show you how to apply qualitative and quantitative reasoning to today's OM and SCM concepts.